A pilot investigation of the effect of electronic cigarettes on smoking behavior among opioid-dependent smokers. (April 2019) - Felicione, Nicholas J.; Enlow, Paul; Elswick, Daniel; Long, Dustin; Sullivan, C.R.; Blank, Melissa D.
Abstract: Introduction: Compared to the general population, smoking rates are 2–4 times higher among individuals with opioid use disorders (OUDs). These smokers also have poor long-term cessation rates, even with pharmacotherapy or other interventions. Low success rates with traditional approaches may prompt smokers with OUDs to try more novel products like electronic cigarettes (ECIGs). This pilot study was designed to examine the feasibility, acceptability, and effect of ECIGs on smoking behavior among smokers with OUD. Methods: Participants ( N  = 25) were daily smokers receiving buprenorphine/naloxone for OUD at an outpatient clinic. They were randomized to use a second-generation ECIG (0 or 18 ng/ml nicotine) ad libitum for two weeks while completing assessments via text messaging daily, and also via in-person visits at baseline, end of the two-week intervention, and a 4-week follow-up. Results: Feasibility was evidenced by high enrollment (93.9%) and retention (70.9%) rates. ECIG adherence was relatively high as measured by self-report (80.6% active, 91.7% placebo), while the average volume of liquid used per week was low (~3 ml). Both ECIG doses produced reductions in self-reported cigarettes per day that were not supported by average carbon monoxide levels. Biologically-confirmed smoking abstinence was observed in 8% of participants. Conclusions: Preliminary results suggest that smokers with OUD are interested in using ECIGs, but their adherence may be less than ideal. Poor medication adherence rates are often observed in this disparate population, and future work should consider the use of other ECIG device types and a combination of methods to verify and quantify ECIG use. Highlights: High rates of study enrollment (93.9%) and retention (70.9%) were observed ECIG adherence was high based on self-reports, though the volume of liquid used was low Self-reported reductions in cigarettes per day, but not expired air CO levels, were observed Biologically-confirmed abstinence was observed for 8% of participants, similar to previous work with smokers with OUD